Наша Таня громко плачет - Барто Агния Львовна (Серия "Любимые книги детства", 2019)
Экземпляры: Ф4 (20220203ԁ) / Инвентарный номер: 62517 / Цена: 100.00 / Сис.шифр: Д / Авт.знак: Б 26 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6